2023
DOI: 10.1128/mbio.03153-22
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and strain-specific resistance evolution of Staphylococcus aureus against inhibitory molecules secreted by Pseudomonas aeruginosa

Selina Niggli,
Lukas Schwyter,
Lucy Poveda
et al.

Abstract: Pseudomonas aeruginosa and Staphylococcus aureus frequently occur together in polymicrobial infections, and there is evidence that their interactions negatively affect disease outcome in patients. At the molecular level, interactions between the two bacterial species are well-described, with P. aeruginosa usually being the dominant species suppressing S. aureus through a variety of inhibitory molecules. However, in chronic infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…newly recognized role for the gltT gene influencing S. aureus and P. aeruginosa interactions Interactions between S. aureus and P. aeruginosa have proven to be complex, and dependent on environment and strain background [12,16,[38][39][40][41]. Studies have implicated factors such as the P. aeruginosa mucoid phenotype, Pseudomonas excreted compounds or toxins, and S. aureus metabolic pathways such as the production of acetoin, as important factors in the interspecific interactions between S. aureus and P. aeruginosa [7,8,16,38,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…newly recognized role for the gltT gene influencing S. aureus and P. aeruginosa interactions Interactions between S. aureus and P. aeruginosa have proven to be complex, and dependent on environment and strain background [12,16,[38][39][40][41]. Studies have implicated factors such as the P. aeruginosa mucoid phenotype, Pseudomonas excreted compounds or toxins, and S. aureus metabolic pathways such as the production of acetoin, as important factors in the interspecific interactions between S. aureus and P. aeruginosa [7,8,16,38,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the laboratory strains, S. aureus USA300 JE2 and P. aeruginosa PAO1, interact competitively when cultured together and that those interactions are greatly influenced by factors such as alginate and quinolone production by PAO1 [9][10][11]. Additionally, it has been observed that JE2 can adapt to secreted factors present in PAO1 supernatant in short-term evolution experiments [12]. Other studies have shown that adaptations to specific compounds such as 2-heptyl-4-hydroxyquinoline-N-oxide (HQNO) and pyocyanin may impact the antibiotic resistance profiles of either species [9,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Data File 02), we would not expect similar selective pressures in our assay. In a separate study, S. aureus evolved in the presence of P. aeruginosa supernatant showed strain-dependent acquisition of resistance that converged on staphyloxanthin (carotenoid) production and the formation of small colony variants (SCVs) (110). Interestingly, in two different strains, 1 out of 5 populations each encoded a mutation in codY, one being intergenic and the other a non-synonymous mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, interactions between key pathogens like P. aeruginosa and Staphylococcus aureus have been extensively studied as these species often co-occur in patients (Hotterbeekx et al, 2017; Ibberson and Whiteley, 2020; Limoli and Hoffman, 2019; Nguyen and Oglesby-Sherrouse, 2016). Research focused on various aspects including molecular mechanisms of interactions (Armbruster et al, 2016; Limoli et al, 2019; Yarrington et al, 2024; Zarrella and Khare, 2022), variation in interactions between different strains and across environments (Bernardy et al, 2022; Niggli et al, 2021; Niggli and Kümmerli, 2020), the evolution of interactions (Niggli et al, 2023; Tognon et al, 2017) and the consequences of interactions for the host (Orazi and O’Toole, 2017; Radlinski et al, 2017; Rezzoagli et al, 2020). Interactions among other pathogens (e.g.…”
Section: Introductionmentioning
confidence: 99%